Implementasi Metode Demonstrasi PAI Materi Thaharah Untuk Meningkatkan Hasil Belajar Siswa Kelas VIII Mts Ma’arif Kaliwiro - Frisca Anasyaputri; Maryono Maryono; Salis Irvan Fuadi (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
Methods Demonstration Improving Student Learning Outcomes in grade VIII MTs Ma’arif Kaliwiro. This study aims to determine differences student achievement between the experimental class using a demonstration method and the control class using a conventional method. (2) To find out how much student achievement increased between the experimental class using demonstration method and the control class using a conventional method. This research is a quantitative research with a type of field research namely an experiment with a quasy-experimental design. The sample in this study was taken by simple random sampling technique. The population in this study were all grade VIII strudents of MTs Ma’arif Kaliwiro 2022/2023 academic year. Two classes were taken as samples, one experimental class and the other one control class. The data collection technique in research was in the form of test, namely pretest and posttest aside from that the documentation. Hypothesis testing in this study used the t-test and N-gain test with the help of SPSS.